Influencia de medios audiovisuales en la autonomía de las clases virtuales en niños de cinco años de la Institución Educativa N° 259 Gotitas de amor, Nauta 2022 - Pacaya Guerra, Lesly Fiorela (2023)
The objective of this research was to analyze the influence of the use of audiovisual media in the autonomy of virtual classes in five-year-old children of the Initial Educational Institution N° 259 "Gotitas de Amor" Nauta 2022. The type of study is non-experimental with a descriptive correlational design, considering a population of forty-one and this same population as the sample, for which nonprobabilistic sampling was used. The technique used was observation and the instrument used was the checklist., being structured for each variable with its respective dimension and item; likewise, they were validated by three teachers with expertise in the subject and to obtain the reliability the Cronbach's alpha statistic was used, which indicates that they are reliable. Statistical graphs were used to analyze the tables of data percentages and averages. The most relevant conclusions were the following: The use of audiovisual media has a significant influence on autonomy in virtual classes of five-year-old children of the Institución Educativa Inicial N° 259 "Gotitas de Amor" Nauta 2022.